Effects of crocin on brain oxidative damage and aversive memory in a 6-OHDA model of Parkinson’s disease - Rajaei,Z (2016)
ABSTRACT The purpose of the present study was to investigate the effect of crocin on brain oxidative damage and memory deficits in a 6-hydroxydopamine (6-OHDA) model of Parkinson’s disease. Male Wistar rats were subjected to unilateral injection of 6-OHDA (16 µg) into the medial forebrain bundle and treated with crocin (30 and 60 mg/kg) for six weeks. The rats were tested for memory performance at six weeks after 6-OHDA infusion, and then were killed for the estimation of biochemical parameters. The increase in thiobarbituric acid reactive substances (TBARS) and nitrite levels in the hippocampus were observed in the 6-OHDA lesioned rats, which was accompanied by memory deficits in a passive avoidance test at the end of week 6. Moreover, treatment with crocin decreased TBARS and nitrite levels in the hippocampus, and improved aversive memory. The present study conclusively demonstrated that crocin acts as an antioxidant and anti-inflammatory agent in the hippocampus of parkinsonian rats and could improve aversive memory through its properties.